Atypical Social Referencing in Infant Siblings of Children with Autism Spectrum Disorders. - Cornew, Lauren; Dobkins, Karen; Akshoomoff, Natacha; McCleery, Joseph; Carver, Leslie (Journal of Autism & Developmental Disorders, 2012)
Social referencing was investigated in 18-month-old siblings of children with autism spectrum disorders (ASD; 'high-risk infants'). Infants were exposed to novel toys, which were emotionally tagged via adults' facial and vocal signals. Infants' information seeking (initiation of joint attention with an adult) and their approach/withdrawal behavior toward the toys before versus after the adults' emotional signals was measured. Compared to both typically developing infants and high-risk infants without ASD, infants later diagnosed with ASD engaged in slower information seeking, suggesting that this aspect of referencing may be an early indicator of ASD. High-risk infants, both those who were and those who were not later diagnosed with ASD, exhibited impairments in regulating their behavior based on the adults' emotional signals, suggesting that this aspect of social referencing may reflect an endophenotype for ASD.